General Synod of the Church of Ireland. (11th December 2014) - Davey, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> In this, the final year of the current triennium, the General Synod met again in Christ Church Cathedral, Dublin. Whether it will return to this venue, and if so how often, is open to doubt since the Synod directed that efforts be made to find a more satisfactory meeting place in Dublin having regard to the comparative costs of its regular meetings at the alternative venue in Armagh.